Testing self-supportive strategies to regulate autonomy and motivation. - Barbara Flunger; Lau Lilleholt; Robert Böhm; Anouk Verdonschot; Tamara van Gog; Ingo Zettler (PLoS ONE)
People regularly encounter situations in which they have to engage in tasks they find boring or irrelevant, in which case their autonomy-the need to act in ways that are meaningful for oneself-is impeded. When there is no motivational support available, individuals need to find ways to overcome their motivational barriers by themselves. Applying autonomy-regulation strategies may be effective for increasing autonomy and particularly the more adaptive types of motivation (i.e., intrinsic and internalized). Testing this idea, we investigated whether individuals apply self-supportive strategies to boost their feelings of autonomy and motivation in two studies via cross-sectional survey samples (overall N = 2,344). We analyzed how autonomy regulation strategies were associated with theoretically related variables via Structural Equation Modeling (SEM). In Study 1, the self-reported use of autonomy regulation strategies was strongly positively associated with intrinsic and internalized types of motivation, weakly positively correlated with introjected avoidance motivation, and not associated with external motivation. In Study 2, we introduced two dilemmas concerning motivational problems individuals face when engaging in tasks and being assigned a task, respectively. Results indicate that individuals report using general strategies of autonomy regulation to achieve fulfillment of autonomy and intrinsic motivation, next to more specific autonomy regulation strategies regarding specific dilemmas. Our results show that it would be worthwhile to investigate if stimulating individuals to use autonomy regulation strategies would positively affect their motivation (e.g., in job or study contexts), and that in doing so, it is important to consider both specific context effects on autonomy regulation as well as individual preferences for general strategies used to regulate one's autonomy.